Traditional leaders of the Bakgatla-ba-ga-Kgafela and their succession story (Historia, 2021)
The name Bakgatla is shared by several groups of Bantu-speaking people inhabiting the central and western districts of the Transvaal and the south-eastern parts of Botswana.
Keywords: Bakgatla-ba-ga-Kgafela